STRATEGI PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT DI PULAU SAMALONA, MAKASSAR - Nurdin, Nurdin (Jurnal Master Pariwisata (JUMPA); Volume 03, Nomor 01, Juli 2016, 2016)
Samalona Island is one of the tourist destinations in Makassar. Therefore it needs an effective strategy for the tourism development by empowering local communities.The research aims were identifying and analyzing potency and tourist attraction, community participation and formulate development strategies.This research applied theory of tourism area life cycle, theory of planning and theory of participation. The data were collected by documentation studies, observation and in–depth interviews.Data were analyzed by descriptive qualitative method and matrix SWOT.The results suggested that Samalona Island is very feasible to be developing as a community-based tourism destination with the natural and socio-cultural potencies.The development of those obstacles are by applied strategies are as follows; strategy of strength–opportunity (S–O) with development strategy of tourism destination and development strategy of tourism attraction, strategy of strength–threat (S–T) with improvement strategy of environmental quality, development strategy of sustainable tourism, strategy of weakness–opportunity (W–O) with promotion strategy of tourism destination, whereas strategy of weakness–threat (W–T) with development strategy of human resources and development strategy of institutional and management of destination.
Keywords: strategy, development, community-based tourism, Samalona Island